Evaluate (6*2) + (12*2)
36 The key concept here is understanding the order of operations. In this equation, the items within the parentheses should be solved first. (6*2) = 12 (12*2) = 24 So, we rewrite the equation as: 12 + 24 From here, this becomes a normal addition problem of 12 and 24, leading us to our final answer of 36.
Solve for n: 6n + 12 = 6
n = -1 The goal here is to isolate "n" on one side of the equation. To do that, we start by subtracting 12 from both sides. This becomes: 6n = -6 Now, to solve for n, we divide both sides of the equation by 6. n = -1
Evaluate the following expression when x=4 and y=3 5x+y^2−xy
17 Using the defined values for x and y, start by rewriting the equation substituting those values. 5*4+3^2-4*3 Then, determine the value for each individual part. 20+9-12 Finally, combine these values to reach the final answer.